2009
DOI: 10.1371/journal.pone.0004635
|View full text |Cite
|
Sign up to set email alerts
|

Lung Volume, Breathing Pattern and Ventilation Inhomogeneity in Preterm and Term Infants

Abstract: BackgroundMorphological changes in preterm infants with bronchopulmonary dysplasia (BPD) have functional consequences on lung volume, ventilation inhomogeneity and respiratory mechanics. Although some studies have shown lower lung volumes and increased ventilation inhomogeneity in BPD infants, conflicting results exist possibly due to differences in sedation and measurement techniques.Methodology/Principal FindingsWe studied 127 infants with BPD, 58 preterm infants without BPD and 239 healthy term-born infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
94
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 48 publications
17
94
5
Order By: Relevance
“…Thus, the pathophysiology of the premature lung is complex, with many factors contributing and interacting. Whether the association of minute ventilation with Scond indicates an adaptive mechanism upon increased Scond, or a primary regulatory response cannot be answered by our data [15]. The mechanism for this pattern of ventilation inhomogeneity could be explained by the fact that these children were born during the late canalicular-early saccular period of lung development, when the peripheral conducting airways are already developed and thus vulnerable, while the alveolar regions develop later and continue to grow after birth [35].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, the pathophysiology of the premature lung is complex, with many factors contributing and interacting. Whether the association of minute ventilation with Scond indicates an adaptive mechanism upon increased Scond, or a primary regulatory response cannot be answered by our data [15]. The mechanism for this pattern of ventilation inhomogeneity could be explained by the fact that these children were born during the late canalicular-early saccular period of lung development, when the peripheral conducting airways are already developed and thus vulnerable, while the alveolar regions develop later and continue to grow after birth [35].…”
Section: Discussionmentioning
confidence: 80%
“…However, few studies have specifically examined ventilation inhomogeneity as a biomarker of peripheral lung function, and with inconclusive results. Two studies in preterm infants showed contradictory results, one with elevated ventilation inhomogeneity [14] and the other with no sign for ventilation inhomogeneity [15]. At school-age only one study examined ventilation inhomogeneity in former preterm children, showing mildly elevated ventilation inhomogeneity in 58% of them [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lung function abnormalities are detectable early in life after premature birth [4,29], and carry a substantial risk of long-term respiratory disease [30] because a poor lung function in the first months of life is known to track over time with a greater risk of airway obstruction in childhood [31] and young adulthood [32].…”
Section: Discussionmentioning
confidence: 99%
“…EEL in spontaneously breathing preterm infants is maintained above passive resting volume through a combination of mechanisms which include braking of the expiratory flow to prolong the time constant of the respiratory system, decreasing the expiratory time by increasing respiratory rate, and using respiratory muscle activity to dynamically elevate EEL (30,31). In the infants on CPAP there was an increased EEL at 2 h which corresponded with improved homogeneity and increased regional ventilation of the posterior lung.…”
Section: Articlesmentioning
confidence: 99%